(untitled) (Revista LIDER, 2019)
The main objective of this work is to reflect on the modes of heritage activation and the processes of constitution of the supply of tourism in sites that have been inscribed in the World Heritage List (UNESCO). For this, the tourist use of the Guaraní Jesuit Missions of the Argentine Republic is analyzed and, with it, a series of contradictions are combined. Specifically, it is a case that has the highest international recognition in terms of heritage along with a recognized tourist attractiveness but, in practice, coexists with numerous management and, especially, development dilemmas. Methodologically, it combines a deductive path originated from an interdisciplinary bibliographic analysis, linked to the relationship between tourism and world heritage, including a reflection on the paradigms of heritage activation and its relationship with development. In this sense, it is an antecedent that highlights the need to develop cultural, heritage and tourism policies in an interdependent way, understanding that this has important consequences in the development of the local communities that inhabit these territories. As a reflexive strategy, we propose to rethink the concept of “culture”, understanding it as a process rather than as a characteristic, thing or entity defined and inherent (Wright, 1998) and, with it, the consequences that may arise depending on the socio-economic, historical context that may particularly be representative of a whole heritage site.